Evaluation of a new model of short-term palliative care for people severely affected with multiple sclerosis: a randomised fast-track trial to test timing of referral and how long the effect is maintained. Issue 1033 (6th October 2011) - Higginson, Irene J; Costantini, Massimo; Silber, Eli; Burman, Rachel; Edmonds, Polly
Abstract : Aims: In this randomised fast-track phase II trial, the authors examined (1) whether the timing of referral to short-term palliative care (PC) affected selected outcomes, and (2) the potential staff-modifying effect of the short-term PC intervention (whether the effects were sustained over time after PC was withdrawn). Methods: PC comprised a multiprofessional PC team that provided, on average, three visits, with all care completed by 6 weeks. Recruitment commenced in August 2004 and continued for 1 year. Follow-up was performed for 6 months in both groups. Outcomes were a composite measure of five key symptoms (pain, nausea, vomiting, mouth problems and sleeping difficulty) using the Palliative care Outcome Scale–MS Symptom Scale, and care giver burden was measured using the Zarit (Care Giver) Burden Interview (ZBI). Results: 52 patients severely affected by multiple sclerosis were randomised to receive PC either immediately (fast-track group) or after 12 weeks (control group). Patients had a high level of disability (mean Expanded Disability Status Scale: 7.7; median: 8; SD: 1). Following PC, there was an improvement in Palliative care Outcome Scale–MS Symptom Scale score and ZBI score. A higher rate of improvement in ZBI score was seen in the fast-track group. After withdrawal of PC, effects were maintained at 12 weeks, but not at 24 weeks. Conclusions: Receiving PC earlier has a similar effect on reducing symptoms but greater effects on reducing care giver burden, compared to later referral. In this phase II trial, the authors lacked the power to detect small differences. The effect of PC is maintained for 6 weeks after withdrawal but then appears to wane. Trial Registration Number: National Institutes of Health, USA, http://www.Clinicaltrials.gov, NCT00364936 .